The Effects of Chronic Preoperative Steroid Therapy on Perioperative Complications Following Elective Posterior Lumbar Fusion. Issue 8 (December 2018) - Ranson, William A.; White, Samuel J. W.; Cheung, Zoe B.; Mikhail, Christopher; Ye, Ivan; Kim, Jun S.; Cho, Samuel K.
Study Design: Retrospective cohort study. Objectives: Chronic steroid therapy is used in the treatment of various inflammatory and autoimmune conditions, but it is known to be associated with adverse effects. There remains a gap in the literature regarding the role of chronic steroid therapy in predisposing patients to perioperative complications following elective posterior lumbar fusion (PLF). We aimed to identify the effects of chronic preoperative steroid therapy on 30-day perioperative complications in patients undergoing PLF. Methods: A retrospective analysis was performed using the 2011-2014 American College of Surgeons National Surgical Quality Improvement Program (ACS-NSQIP) database. We identified 22 903 patients who underwent elective PLF. There were 849 patients (3.7%) who received chronic preoperative steroid therapy. Univariate and multivariate analyses were performed to examine steroid therapy as an independent risk factor for 30-day perioperative complications. A subgroup analysis of patients on chronic steroid therapy was then performed to identify additional patient characteristics that further increased the risk for perioperative complications. Results: Chronic preoperative steroid therapy was an independent risk factor for 7 perioperative complications, including superficial surgical site infection (SSI), deep SSI, wound dehiscence, urinary tract infection, pulmonary embolism, nonhome discharge, and readmission. Subgroup analysis demonstrated that morbid obesity further predisposed patients on chronic steroid therapy to an increased risk of superficial SSI and wound dehiscence. Conclusions: Patients on chronic preoperative steroid therapy are at increased risk of multiple perioperative complications following elective PLF, particularly surgical site complications and venous thromboembolic events. This risk is further elevated in patients who are morbidly obese.